Operation Testing of an Advanced Personalized Ventilation System - Imre Csáky; Tünde Kalmár; Ferend Kalmár (Energies, 2019)
Using personalized ventilation systems in office buildings, important energy saving might be obtained, which may improve the indoor air quality and thermal comfort sensation of occupants at the same time. In this paper, the operation testing results of an advanced personalized ventilation system are presented. Eleven different air terminal devices were analyzed. Based on the obtained air velocities and turbulence intensities, one was chosen to perform thermal comfort experiments with subjects. It was shown that, in the case of elevated indoor temperatures, the thermal comfort sensation can be improved considerably. A series of measurements were carried out in order to determine the background noise level and the noise generated by the personalized ventilation system. It was shown that further developments of the air distribution system are needed.